Development of glycerol-based metal-free carbon materials for environmental catalytic applications - Ribeiro, Rui (2014)
A thermally stable and non-porous carbon material (SBET= 10 m2g−1and no micropores), with low ashcontent and basic character, was produced by partial carbonization of glycerol with sulphuric acid fol-lowed by calcination under inert atmosphere. Further thermal activation in air atmosphere at differenttemperatures (from 150 to 350◦C) leads to materials with less basic character and to a tremendous evolu-tion of the porosity, mostly microporosity (SBET= 598 m2g−1and VMic= 0.24 cm3g−1). Experiments showthat metal-free carbon materials synthesized by this approach can be highly active catalysts for the cat-alytic wet peroxide oxidation (CWPO) process when the surface chemistry and textural properties areadequately tuned. Effective catalytic degradation of 2-nitrophenol (80% conversion) was achieved withthe material treated under air atmosphere at 300◦C, even when operating under a high pollutant/catalystmass ratio, opening a window of opportunity for added-value crude glycerol-derived products. Further-more, catalyst activity was effectively recovered by a simple oxidative thermal regeneration procedure.